The role of business visits in fostering R&D investment - Marco Vivarelli; Mariacristina Piva; Massimiliano Tani (Global Labor Organization (GLO), 2025)
Labor mobility is considered a powerful channel to acquire external knowledge and trigger complementarities in the innovation and R&D investment strategies; however, the extant literature has focused on either scientists' mobility or migration of high-skilled workers, while virtually no attention has been devoted to the possible role of short-term business visits. Using a unique and novel database originating a country/sector unbalanced panel over the period 1998-2019 (for a total of 8,316 longitudinal observations), this paper aims to fill this gap by testing the impact of BVs on R&D investment. Results from GMM-SYS estimates show that short-term mobility positively and significantly affects R&D investments; moreover, our findings indicate - as expected - that the beneficial impact of BVs is particularly significant in less innovative countries and in less innovative industries. These outcomes justify some form of support for BVs within the portfolio of the effective innovation policies, both at the national and local level.
Keywords: O3; F2; J6; 330; Business visits; labor mobility; knowledge transfer; R&D investments